2020
DOI: 10.1155/2020/7601590
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Source Apportionment of Heavy Metals and Physicochemical Parameters: A Case Study of Sapanca Lake Watershed

Abstract: This study was aimed to evaluate the water quality and pollution sources in Sapanca Lake and its tributaries by applying multivariate statistical techniques to physicochemical parameters and toxic metals. For this purpose, the multivariate statistical methods such as principal component analysis (PCA) and absolute principal component score-multiple linear regression (APCS-MLR) model have been employed. It was tried to determine the seasonal pollution sources of physicochemical parameters and toxic metals obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Similar to our findings, Arman et al (2009) have found the highest NO 3 -N values in the 1st and 8th stations, and the highest PO 4 -P values in the 8th station. Ateş et al (2020) have pointed out that lithogenic, agricultural activities, industrial and domestic wastewater, and traffic load around the lake are the main sources responsible for toxic metal pollution and physicochemical parameters regarding the Lake Sapanca water quality. In their study, they have mentioned the importance of the transport of chemicals by surface runoff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our findings, Arman et al (2009) have found the highest NO 3 -N values in the 1st and 8th stations, and the highest PO 4 -P values in the 8th station. Ateş et al (2020) have pointed out that lithogenic, agricultural activities, industrial and domestic wastewater, and traffic load around the lake are the main sources responsible for toxic metal pollution and physicochemical parameters regarding the Lake Sapanca water quality. In their study, they have mentioned the importance of the transport of chemicals by surface runoff.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, various watercourses in the western Mediterranean (Toudjani et al, 2017), North Aegean (Çelekli et al, 2018), and Gaziantep region (Çelekli and Arslanargun, 2019) were studied using these indices. Although there are some studies on Lake Sapanca (Temel, 1996;Akçaalan et al, 2007;Yılmaz and Aykulu, 2010), and on its creeks (Arman et al, 2009;Ateş et al, 2020;Akıner and Akıner, 2021), no studies were done on the diatom flora or diatom indices to evaluate the water quality of the creeks feeding the lake. For this reason, this study aims to assess the ecological status of eight creeks feeding Lake Sapanca using diatom indices developed from different ecoregion and to define the most important environmental factor(s) driving the distribution of epilithic diatom assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…The mineral structure of soil in the lake basin serves as the lithogenic source in this context. Tra c and lithogenic sources lead to the existence of EC in the lake water (Ateş et al 2020). In monthly water quality analyses carried out by Pal et al (2013) for three natural lakes in Mahoba district in the Bundelkhand region of Uttar Pradesh, over a period of 6 months, the highest EC value was recorded in summer, as 823 µS/cm, while the lowest value was recorded in winter, as 518 µS/cm.…”
Section: Variation Of Physicochemical Water Characteristics In Stream...mentioning
confidence: 99%
“…Aluminum stood out as the heavy metal with the highest concentration at all sampling points (3,391 mg/l). The signi cant presence of Al is mostly due to the characteristics of the soil of the region, however (Ateş et al 2020).…”
Section: Variation Of Hm Levels In Ve Major Streams Connected To Lake...mentioning
confidence: 99%
“…Besides this, Kocaeli and Sakarya municipalities also use water [18]. The Lake is faced with pollution and salinity due to the extensive use of freshwater and uncontrolled pollution [19].…”
Section: The Need For Environmental Managementmentioning
confidence: 99%